Chemical Composition of Some Ber CuItivars Leaves - Patel, B T; Shakhela, R R; Kalyanasundaram, N K; Patil, R G; Patel, G A (Annals of Arid Zone, 2016)
Chcmicalcompositonof Icaveof fivcyearold Bcrcultivarsshowedhighestcontentof Ca (2.66%) followcdhy N (2.19%). (1.38%).Mg (0.94%)and P (0.144%).Amongst the micronutrients,higher concentration of Fe(289ugg-1)was recorded compared to Mn(85ugg-1),Zn (24ugg-1 ) and Cli(3.9ugg-1). Correlationof yield was positive with N.Ca.Mg and and negative with P, K, Fe,Zn and Cu.and Mn and negative with P, K, Fe,Zn and Cu.